Grain yield and protein content in different ripening varieties of soft winter wheat using various types and doses of fertilizers - Т. В. Сіліфонов (Plant Varieties Studying and Protection)
Purpose. To study of yield formation and protein content in the grain of different ripening varieties of soft winter wheat under the condition of using various types and doses of fertilizers.